2014
DOI: 10.1038/ismej.2014.16
|View full text |Cite|
|
Sign up to set email alerts
|

Phagotrophy by the picoeukaryotic green alga Micromonas: implications for Arctic Oceans

Abstract: Photosynthetic picoeukaryotes (PPE) are recognized as major primary producers and contributors to phytoplankton biomass in oceanic and coastal environments. Molecular surveys indicate a large phylogenetic diversity in the picoeukaryotes, with members of the Prymnesiophyceae and Chrysophyseae tending to be more common in open ocean waters and Prasinophyceae dominating coastal and Arctic waters. In addition to their role as primary producers, PPE have been identified in several studies as mixotrophic and major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 52 publications
10
113
0
Order By: Relevance
“…The dominance of picoeukaryotes (mainly M. pusilla) under LL and diatoms under HL can also explain the counterintuitively rising Chla:C ratios with increasing light (Table 1). Previous studies have shown low Chla:C ratios in M. pusilla resulting from high energy demand imposed by motility (Halsey et al, 2014) and its mixotrophic nature (McKie-Krisberg and Sanders, 2014). The lower Chla:C under LL in the initial part of the experiment thus may primarily reflect ecological shifts within the species assemblages, rather than photo-physiological effects.…”
Section: Initial High Light Stress Causes Transient Shift In Communitmentioning
confidence: 89%
“…The dominance of picoeukaryotes (mainly M. pusilla) under LL and diatoms under HL can also explain the counterintuitively rising Chla:C ratios with increasing light (Table 1). Previous studies have shown low Chla:C ratios in M. pusilla resulting from high energy demand imposed by motility (Halsey et al, 2014) and its mixotrophic nature (McKie-Krisberg and Sanders, 2014). The lower Chla:C under LL in the initial part of the experiment thus may primarily reflect ecological shifts within the species assemblages, rather than photo-physiological effects.…”
Section: Initial High Light Stress Causes Transient Shift In Communitmentioning
confidence: 89%
“…Furthermore, mixotrophy may facilitate survival during the dark winter period, as suggested for phototrophic flagellates in high-latitude lakes (60,61). The Arctic Micromonas ecotype, which is dominant and widespread in Arctic waters (58,(62)(63)(64), was recently shown to be capable of phagotrophy (65). Living cells of the Arctic Micromonas ecotype have been detected around Spitsbergen even during the polar night (15,40).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that, similar to cyanobacteria, Mamiellales are metabolically active at the aphotic depth with a large fraction of genes assigned to anabolic processes. The upregulation of phagocytosis at 440 m suggests mixotrophy, which is a strategy applied by Micromonas under light or nutrient limitation (McKie-Krisberg & Sanders 2014). Yet, comparable to the results obtained for cyanobacteria at this depth, we detected mostly low expression of organic-compound transporters in Mamiellales (Table S4).…”
Section: Prasinophytes − Mamiellalesmentioning
confidence: 99%